Efficacy and safety of Bufei Huoxue capsules in the management of convalescent patients with COVID-19 infection: A multicentre, double-blind, and randomised controlled trial. (10th February 2022) - Chen, Yuqin; Liu, Chunli; Wang, Tingping; Qi, Jingjing; Jia, Xiaoqing; Zeng, Xiansheng; Bai, Jianling; Lu, Wenju; Deng, Yu; Zhong, Bihua; He, Wenjun; Xing, Yue; et al.
Abstract: Background: As of September 17, 2021, coronavirus disease 2019 (COVID-19) has infected more than 226 million people in a worldwide pandemic, with conservative estimates suggesting that there are more than 204 million convalescent patients with COVID-19. Previous studies have indicated that patients in the recovery phase exhibit decreased function of multiple organs. In China, traditional Chinese medicine (TCM) treatment is recommended in the rehabilitation period of COVID-19; however, the safety and efficacy of such treatment remain to be confirmed. Aim of study: The present study aimed to evaluate the efficacy and safety of Bufei Huoxue (BFHX) in restoring the functional status and exercise tolerance of patients recovering from COVID-19. Methods: A total of 131 patients in the rehabilitation period of COVID-19 infection were randomly divided into a Bufei Huoxue (BFHX) group (n = 66) and a placebo group (n = 65). BFHX or placebo was given orally three times a day (1.4 g/dose) for 90 days. The primary outcomes was to evaluate improvements in exercise tolerance and imaging manifestations on chest computed tomography (CT). Results: After the exclusion of two patients who withdrew prior to receiving any medications, 129 patients were recruited, including 64 patients in the BFHX group and 65 patients in the placebo group. After 3 months of treatment, the BFHX group exhibited greater attenuation of pneumonia lesions on chest CT than the placebo group ( P < 0.05). Improvements in 6-min walk distance (6MWD) relative to baseline were also significantly better in the BFHX group than in the placebo group ( P < 0.01). Scores on the Fatigue Assessment Inventory (FAI) were lower in the BFHX group than in the placebo group ( P < 0.05). Although the rate of adverse events was higher in the BFHX group than in the placebo group (9.38% vs. 4.62%), the difference was not significant ( P = 0.3241). Conclusions: BFHX may exert strong rehabilitative effects on physiological activity in patients recovering from COVID-19, which may in turn attenuate symptoms of fatigue and improve exercise tolerance. Graphical abstract: Image 1 Highlights: This prospective study assessed the efficacy and safety of BFHX in treating patients recovering from COVID-19. BFHX may have strong rehabilitative effects on patients recovering from COVID-19. BFHX reduces fatigue symptoms and improves exercise tolerance.